Gender Participation in Political Geography Issues in Pariaman City, Indonesia - Yaldi, Priyaldi; Erianjoni, Erianjoni (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
: This research study is related to women's participation in political parties in Kota Pariaman. This study explains the women's participation in political parties in Kota Pariaman so that women's opportunities to fulfil the 30% quota in the legislature can be achieved. This study concludes that first, the low of women's participation in political parties is due to the limitations of women in accessing politics themselves and women recruited in political parties only as a complement to management and women are not involved in policymaking. Secondly, the women's participation in political parties will be seen only in party activities that involve women as committee members, while the women who can participate properly are women who have been involved in social organizations and party autonomous organizations. Third, in the activities of political parties, women have some natural constraints and the constraints that are caused by party treatment. The natural constraints that cause limited space for women in political parties are the activities of women as housewives, as wives and as mothers of their children. The constraints that are caused by party treatment is that women are often not accommodated in policy making towards women or the party policies in general.